2021
DOI: 10.3390/ani11061558
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Sperm Management and Fertilization in Zebrafish (Danio rerio (Hamilton))

Abstract: The aim of the present study was to investigate the spontaneous motility of spermatozoa and to optimize sperm collection, short-term sperm storage, and fertilization in zebrafish Danio rerio. The movement of spermatozoon in water was propagated along the flagellum at 16 s after sperm activation then damped from the end of the flagellum for 35 s and fully disappeared at 61 s after activation. For artificial fertilization, milt must be added to an immobilizing solution, which stops the movement of sperm and keep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Frequent studies have shown that fertilization rate positively correlates with sperm volume, sperm density, number of sperm per oocyte, and density of sperm in the water during fertilization [76][77][78][79][80][81][82][83]. One can weigh semen mass, measure semen volume, or count sperm density to evaluate sperm production.…”
Section: Sperm Productionmentioning
confidence: 99%
“…Frequent studies have shown that fertilization rate positively correlates with sperm volume, sperm density, number of sperm per oocyte, and density of sperm in the water during fertilization [76][77][78][79][80][81][82][83]. One can weigh semen mass, measure semen volume, or count sperm density to evaluate sperm production.…”
Section: Sperm Productionmentioning
confidence: 99%